Directional dependence figure of merit analysis of piezoelectric materials. Issue 174 (1st September 2016) - Dutta, Moumita; Bhalla, Amar S.; Guo, Ruyan
ABSTRACT: Efficiency of a piezo-electric transducer is defined by the relative electrical output induced in response to the mechanical stress it encounters. Thus an efficient device design demands an insightful figure of merit analysis of the piezoelectric material used for the sensor fabrication. In this article we have performed a directional dependence figure of merit analysis of some popular piezoelectric materials to determine the cut orientations along which optimal proficiency can be achieved. The materials chosen for the study are PZT-5H, PMN-PT, PZN-PT, PMN-PZT, SbSI, SBN, BT and BCZT such that a comparative perspective can be deduced.